2000
DOI: 10.1093/tropej/46.6.357
|View full text |Cite
|
Sign up to set email alerts
|

Congenital heart disease among school children in Alexandria, Egypt: an overview on prevalence and relative frequencies

Abstract: A study was undertaken to determine the prevalence and relative frequencies of congenital heart diseases diagnosed by echocardiography among school children in Alexandria, Egypt. The study was conducted during a 1-year period (1 May 1995-1 May 1996) at the Students' Health Insurance Hospital, which is a referral center for all health insurance units, providing an echocardiography service. The prevalence of congenital heart diseases (CHD) among school children accounted for 1.01/1,000. There was a male predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
39
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 0 publications
9
39
2
Order By: Relevance
“…12 in south Africa the prevalence of CHD among school children accounted for only 1.01 per 1000 child. [10][11][12][13][14][15] In consistent with the present finding Thakir et al 7 also observed a higher prevalence of CHD among female school going children in the age group of 5-15 years in Shimla hills, India. In contrast there was a male predominance of CHD among school going children from Alexandria, Egypt.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…12 in south Africa the prevalence of CHD among school children accounted for only 1.01 per 1000 child. [10][11][12][13][14][15] In consistent with the present finding Thakir et al 7 also observed a higher prevalence of CHD among female school going children in the age group of 5-15 years in Shimla hills, India. In contrast there was a male predominance of CHD among school going children from Alexandria, Egypt.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast there was a male predominance of CHD among school going children from Alexandria, Egypt. 10,11 The observed high prevalence of operable CHD among school going girls may indicate a negligence of raring up of our female babies than that of their male counterparts. Actually in most of our families boys get more care or importance than that of girls in terms of their feeding, academic education, health cheek up irrespective of the social status of family in the society.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…2 Meberg et al, [61] Karachi 1987-1992 4 Hassan et al, [62] Central Australia 1993-2000 17. 5 Bolisetty et al, 63 South Australia 1993-2000 12 Annual report 2000 [64] Oman 1994-1996 7.1 Subramanyan et al, [65] Bosnia 1994-1999 6.12 Begic et al, [66] Egypt 1995-1996 1.01 Bassili et al, [67] Shimla 1995 2. 25 Thakur et al, [8] Saudi Arabia 1997-2000 2.4 Alabdulgader [68] New Delhi 2001 4.…”
Section: Classification Of Chdsmentioning
confidence: 99%